2023
DOI: 10.1182/bloodadvances.2022009435
|View full text |Cite
|
Sign up to set email alerts
|

Risk of infections associated with the use of bispecific antibodies in multiple myeloma: a pooled analysis

Abstract: The use of bispecific antibodies (BsAbs) in the treatment of relapsed/refractory multiple myeloma (MM) is showing early promising overall response rates in heavily pre-treated patients. Infectious complications related to the use of BsAbs are not well described. We conducted a pooled analysis that included all single agent BsAbs used in MM with no prior use of different BsAbs. A total of 1185 MM patients (number of trials, n=11) were treated with a BsAb in the studied period (71.6% of patients treated with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(34 citation statements)
references
References 20 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…1,5,6,11,[13][14][15] BCMA-bispecific antibodies have been associated with high rates of all-grade and grade ≥3 infection relative to other MM therapies, including non-BCMA-bispecific antibodies. 4,6,11,13,[16][17][18][19] Although these differences in infection risk remain to be fully characterized from a mechanistic perspective, key drivers may include the corresponding decrease in normal plasma cells during BCMA-targeted therapy, which in turn impacts the ability to maintain humoral immunity, 14,20 and T-cell exhaustion, which has been observed following bispecific antibody therapy. 21,22 Time on therapy may potentially also play a role, based on recent data suggesting that the rate of infection may be higher with BCMA-bispecific antibodies than BCMA chimeric antigen receptor T-cell therapy, which is likely related to their prolonged dosing duration given they have the same target.…”
Section: Introductionmentioning
confidence: 99%
“…1,5,6,11,[13][14][15] BCMA-bispecific antibodies have been associated with high rates of all-grade and grade ≥3 infection relative to other MM therapies, including non-BCMA-bispecific antibodies. 4,6,11,13,[16][17][18][19] Although these differences in infection risk remain to be fully characterized from a mechanistic perspective, key drivers may include the corresponding decrease in normal plasma cells during BCMA-targeted therapy, which in turn impacts the ability to maintain humoral immunity, 14,20 and T-cell exhaustion, which has been observed following bispecific antibody therapy. 21,22 Time on therapy may potentially also play a role, based on recent data suggesting that the rate of infection may be higher with BCMA-bispecific antibodies than BCMA chimeric antigen receptor T-cell therapy, which is likely related to their prolonged dosing duration given they have the same target.…”
Section: Introductionmentioning
confidence: 99%
“…With both combinations higher response rates were observed in patients with anti‐CD38 antibody sensitive disease. Serious infections are common in patients treated with BsAbs, with probably a higher rate of such infections with BCMA‐targeting BsAbs compared to BsAbs targeting other MM surface antigens [35], [47], [63]. The incidence and severity of infections may also increase with combination therapy, because combination partners not only have anti‐MM activity, but may also have a negative impact on normal immune cells [74].…”
Section: How To Further Built On These Results?mentioning
confidence: 99%
“…Patients treated with BsAbs have a high frequency of infections which may be related to (1) the high cumulative exposure to immunosuppressive drugs during previous lines of therapy, (2) development of hypogammaglobulinemia due to eradication of normal plasma cells, (3) occurrence of neutropenia, and (4) the development of T-cell exhaustion during long-term BsAb treatment (Figure 3) [61], [62]. In a pooled analysis, non-BCMA targeted BsAbs were associated with lower grade 3/4 infections when compared to BCMA-targeted bispecific antibodies [63].…”
Section: Infectionsmentioning
confidence: 99%
“…59 A recent pooled analysis of 1,185 participants in 11 trials of BsAbs demonstrated high rates of serious or even fatal infection: 24.5% grade 3/4 infection, including 10% grade 3/4 pneumonia. 60 Of the reported deaths, 25% were due to infection. Opportunistic infections not typically observed in the MM population outside of the allogeneic transplant setting have been reported, including Pneumocystis jiroveci pneumonia infection and cytomegalovirus reactivation.…”
Section: Toxicitymentioning
confidence: 99%
“…63 In the four studies reporting on hypogammaglobulinemia, the prevalence was 75%, with nearly half of the patients receiving intravenous immunoglobulin. 60 As the majority of the clinical trials and commercial use of approved products have occurred during the ongoing COVID-19 pandemic, it is also not surprising that deaths from COVID-19 have been reported. 10,31,56,64 The extent to which potential COVID-19induced immune dysregulation, particularly T-cell dysfunction, [65][66][67] affects susceptibility to other infections and MM responsiveness to CAR T-cell and BsAb therapies remains to be determined.…”
Section: Toxicitymentioning
confidence: 99%